Strategi Pengembangan Ternak Itik Petelur di Desa Kamayahan Kecamatan Amuntai Utara Kabupaten Hulu Sungai Utara: Strategy of Development of the Laying Duck in Village Kamayahan Sub Disctrict North Amuntai - Kusumayana, Purna; Nafisah, Saidatun (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2017)
This study aims to determine the development of the laying duck in village Kamayahan sub-district North Amuntai by using the method of data collection by observation method using a survey method. The Data collection by survey method with the population is as much as 16 breeder laying ducks. The result of research indicating that there is internal issue laying duck caused various constraint that is lack of counseling. Level education of low livestock and lack of capital. its solution, the importance of counseling of duck livestock. While for the strategy of its development including capital, conservancy (prevention of disease).